Theophilus of Edessa on the death of Constans II. (October 2020) - Woods, David
Abstract : It is argued that Theophanes the Confessor derives his information concerning the name of the baths where Constans II was allegedly assassinated from Theophilus of Edessa. It is further argued that Theophilus' claim that Andrew deliberately killed Constans by hitting him with a bucket is rather unconvincing and may represent the hypothetical reconstruction of the event by an imperial administration that could not accept that the emperor had died as a result of an unfortunate accident.